2021
DOI: 10.1038/s41598-021-83079-2
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus B sequence analysis reveals a novel early genotype

Abstract: Respiratory syncytial virus (RSV) is a major cause of respiratory infections and is classified in two main groups, RSV-A and RSV-B, with multiple genotypes within each of them. For RSV-B, more than 30 genotypes have been described, without consensus on their definition. The lack of genotype assignation criteria has a direct impact on viral evolution understanding, development of viral detection methods as well as vaccines design. Here we analyzed the totality of complete RSV-B G gene ectodomain sequences publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 54 publications
3
30
0
Order By: Relevance
“…While RSV subgroup was unrelated to disease severity, a lower Ct value (and by inference higher viral load) was observed in children with severe disease. ON1 and BA11 have been reported as the predominant genotypes of RSV A and RSV B subgroups in many places including Australia 18 19. Furthermore, we observed that RSV–PIV3 codetection was associated with greater than twofold higher risk of severe disease compared with the absence of codetection, which was a novel finding.…”
Section: Discussionsupporting
confidence: 60%
“…While RSV subgroup was unrelated to disease severity, a lower Ct value (and by inference higher viral load) was observed in children with severe disease. ON1 and BA11 have been reported as the predominant genotypes of RSV A and RSV B subgroups in many places including Australia 18 19. Furthermore, we observed that RSV–PIV3 codetection was associated with greater than twofold higher risk of severe disease compared with the absence of codetection, which was a novel finding.…”
Section: Discussionsupporting
confidence: 60%
“…Multiple sequence alignment using MUSCLE and further editing were performed using MEGA X [ 18 ]. Reference sequences representing each subtype corresponding to 13 subtypes of RSV-A (n = 111) and 36 subtypes of RSV-B (n = 185) were retrieved from GenBank by referring to relevant publications [ 10 , 11 , 16 ] ( S1 and S2 Tables). Neighbor-joining (NJ) trees of RSV-A and RSV-B were constructed using the maximum composition likelihood model provided in MEGA X, followed by construction of maximum likelihood (ML) trees of RSV-A and RSV-B with the selected most suitable nucleotide substitution model, TN93 + G. Statistical significance of the tree topology was tested by bootstrapping in 1,000 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…The categorization into specific genotypes is useful because the genetic variability of RSV is believed to be responsible for its ability to infect hosts repeatedly [ 9 ]. There are 13 genotypes (GA1-GA7, NA1-NA4, ON1, and SAA1) identified for RSV-A and at least 37 genotypes for RSV-B (GB1, GB2, GB3, GB4, GB5, GB6, GB12, GB13, SAB1, SAB2, SAB3, SAB4, URU1, URU2, CB1, THB, BA1, BA2, BA3, BA4, BA5, BA6, BA7, BA8, BA9, BA10, BA11, BA12, BA13, BA14, BA-C, BA-CCA, BA-CCB, JAB1, NZB1, and NZB2) so far worldwide [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of deep sequencing approaches subsequently allowed for the broader characterization of RSV diversity. 40 Within these antigenic groups, there have been 37 identified genotypes documented for RSV-B 41 and 13 distinct genotypes documented for RSV-A. 42 , 43 The evolutionary rates for both subtypes differ from one another, with RSV-A proposed to have a lower rate at 1.48 × 10 – 3 nucleotide substitutions/site/year as opposed to RSV-B at 1.92 × 10 – 3 substitutions/site/year.…”
Section: Introductionmentioning
confidence: 99%